Analisis Efisiensi Penggunaan Modal Kerja Pada PT Asahimas Flat Glass Tbk - Susilawati Manullang; Aswin Akbar (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study is to see the efficiency in the use of PT working capital. Asahimas Flat Glass Tbk, by using the Financial Ratio in analyzing the efficiency. In this research, it is known that there is an inaccuracy in the source of the use of working capital in 2016-2018. When viewed from the efficiency ratio of working capital use and when compared with the standard measurement of the efficiency of working capital use, then seen from the liquidity ratio in 2016-2017 is good while in 2018 is quite good, the activity ratio for the accounts receivable turnover is less efficient, even for the Inventory turnover is quite efficient and the capital turnover ratio is quite efficient, and seen from the profitability ratio for return on assets and return on equity ratio in 2016 is quite effective and in 2016-2018 is less effective.